2018
DOI: 10.1186/s12864-018-5109-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of Cd-responsive maize and rice transcriptomes highlights Cd co-modulated orthologs

Abstract: BackgroundMetal tolerance is often an integrative result of metal uptake and distribution, which are fine-tuned by a network of signaling cascades and metal transporters. Thus, with the goal of advancing the molecular understanding of such metal homeostatic mechanisms, comparative RNAseq-based transcriptome analysis was conducted to dissect differentially expressed genes (DEGs) in maize roots exposed to cadmium (Cd) stress.ResultsTo unveil conserved Cd-responsive genes in cereal plants, the obtained 5166 maize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 94 publications
0
14
0
Order By: Relevance
“…The WRKY transcription factor family is one of the most important regulator families reported to be involved in a variety of heavy metal stresses. For example, several studies have revealed the differential transcript expression of WRKY transcription factors under Cd stress in different plant species (Yang et al, 2016;Hong et al, 2017;Cheng et al, 2018;Han et al, 2019;Sheng et al, 2019). An increasing number of WRKYs that were identified to confer Cd tolerance in plants also exemplify the importance of heavy metal tolerance in plants.…”
Section: Discussionmentioning
confidence: 99%
“…The WRKY transcription factor family is one of the most important regulator families reported to be involved in a variety of heavy metal stresses. For example, several studies have revealed the differential transcript expression of WRKY transcription factors under Cd stress in different plant species (Yang et al, 2016;Hong et al, 2017;Cheng et al, 2018;Han et al, 2019;Sheng et al, 2019). An increasing number of WRKYs that were identified to confer Cd tolerance in plants also exemplify the importance of heavy metal tolerance in plants.…”
Section: Discussionmentioning
confidence: 99%
“… 131 GAD genes are uniformly up-regulated in maize and rice roots by Cd stress, and the overexpression of ZmGAD1 and ZmGAD2 in Cd-sensitive yeast and tobacco leaves enhances Cd tolerance in the host cells. 132 All of the aforementioned studies indicate that GABA content does not always increase in response to different metal stresses and may be more related to metal concentrations. Furthermore, high GABA content does not always enhance plant tolerance to metal stress.…”
Section: Abiotic and Biotic Stressmentioning
confidence: 99%
“…Previous study conducted in maize and rice plants have revealed that cd-responsive orthologous are conserved in both plants. Among which ZmGAD1 gene, responsible for glutamate decarboxylase (GAD) enzyme (a key enzyme in GABA biosynthesis) has been introduced as a novel Cd-responsive gene and successfully conferred with Cd tolerance in yeast 75 . Here we have focused on GABA modulatory effect on PAs as different line of the tolerance pathway in maize plants.…”
mentioning
confidence: 99%